Correlation between Pesticide Exposure and Cholinesterase Level of Sprayer Workers in PT. Langkat Nusantara Kepong Gohor Lama - Dealita Khairani Daulay; Gerry Silaban; Taufik Ashar (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Pesticides are toxic substances which have some negative impact on human health problems. Cholinesterase enzymes play a role in keeping the muscles, glands and nervous system working harmoniously. The high and low activity of cholinesterase enzyme is an indicator of the level of poisoning in the human body and can be used as an indication of the presence of pesticides in the blood. The purpose of this study was to analyse the relationship of pesticide exposure with cholinesterase levels in the blood of pesticide spraying workers at PT. Langkat Nusantara Kepong Gohor Lama. The research method used is Cross-Sectional at PT. Langkat Nusantara Kepong Gohor Lama with a total sample of 65 workers was obtained by Simple Random Sampling. Information was obtained through interviews with questionnaire aids and cholinesterase examination using a tintometer kit. Based on the results of the analysis using chi-square obtained exposure to pesticides associated with cholinesterase levels in the blood of pesticide sprayers. The result of this study shows that the level of cholinesterase is significantly related to the length of service (p = 0.004) and the use of Personal Protective Equipment (PPE) (p = 0.002). Suggestions for workers to be more obedient in using PPE in the workplace to minimize exposure to pesticides that enter the body, for companies to pay more attention to the feasibility of PPE that is replacing damaged PPE, make rules or sanctions if workers are negligent and do not use PPE that has been provided and workers with abnormal levels of cholinesterase should be moved temporarily to a minimum of chemical work and companies are advised to use environmentally friendly pesticides so as not to endanger workers, animals and non-targeted insects.